PENGARUH PRODUK, HARGA, DAN KUALITAS PELAYANAN SPBU TERHADAP MINAT BELI ULANG BBM JENIS PERTAMAX YANG DIMEDIASI OLEH KEPUASAN KONSUMEN DI KABUPATEN TALAUD - Korayan, Jeremi Zefanya; Haryono, Budi; Saparso (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Fuel is a commodity that plays a very important role in the Indonesian economy. The increasing need for fuel is closely related to economic development and increasing population. This research seeks to identify the factors that influence the interest in purchasing Pertamax fuel through determining the research objective, namely to determine the influence of product, price and service quality at petrol stations on interest in repurchasing Pertamax fuel, mediated by consumer satisfaction in Talaud Regency. The research method used is a quantitative method with a survey questionnaire. The respondents to this research were 120 Pertamax fuel consumers in Talaud Regency. In this research, the data was analyzed using the variance-based Structural Equation Model (SEM) method, namely Partial Lest Square (PLS). The results of this research prove that product, price, service quality and consumer satisfaction have a significant positive effect on interest in repurchasing Pertamax fuel in Talaud Regency. In this research, consumer satisfaction is the most dominant variable in influencing consumers repurchase interest. Consumer Satisfaction is not only a variable that directly influences Repurchase Intention, but is also proven to be able to contribute in mediating the influence of other independent variables on Repurchase Intention for Pertamax BBM. The second variable that also dominantly influences consumers' repurchase interest is product. Consumers evaluate products based on expectations of performance, benefits and quality. Products also contribute indirect influence through the mediation of Consumer Satisfaction in influencing Repurchase Intention. The third variable that has an influence on consumer repurchase interest is service quality. The quality of gas station service is an important aspect evaluated by consumers. In this research, price is the last variable that influences repurchase interest in Pertamax fuel. In fact, the direct influence of Price on Repurchase Intention is not greater than the indirect influence of Price on Repurchase Intention through the mediation of Consumer Satisfaction. Keywords: Product, Price, Service Quality, Consumer Satisfaction, Repurchase Intention